Characterization of the Second Generation Cryopreserved Dendrobium Bobby Messina Using Histological and RAPD Analyses - Antony, Jessica Jeyanthi James; Leong, Kah Wai; Oyunbileg, Yungeree; Subramaniam, Sreeramanan (National University of Mongolia, 2015)
This study was conducted to detect the morphological, histological and molecular diff erences in the second generation of the PVS2 cryopreserved Dendrobium Bobby Messina [DBM] (18 months old culture) plantlets. Morphological analyses indicated that similarities and diff erences in cryopreserved DBM plantlets comparing to control stock culture based on selected morphological criteria. Morphological criteria, such as root length, number of shoot per explant and shoot length displayed diff erences, while the other three criteria, leaf diameter, leaf length and PLBs size were similar in cryopreserved compared to the control stock culture plant. Higher amount of homogenous cell population and denser cytoplasm were observed in cryopreserved PLBs compared to control stock culture PLBs based on histological analysis. This suggests the existance of somatic embryogenesis development mechanism taking place during the recovery and regeneration of the cryopreserved PLBs. However, RAPD analyses based on 10 primers indicated that cryopreserved DBM regenerated from vitrifi cation method generated a total of 20 to 39.9% polymorphic bands as compared to stock culture indicating potential somaclonal variation. Hence, an increase percentage of polymorphics bands in cryopreserved plantlets 18 months post cryopreservation as compared to previous report of 10% polymorphic bands in cryopreserved DBM 3 months post cryopreservation.